2009
DOI: 10.1103/physrevb.80.184424
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the magnetic anisotropy contributions of cobalt nanowires

Abstract: We report on the magnetic properties and the crystallographic structure of the cobalt nanowire arrays as a function of their nanoscale dimensions. X-ray diffraction measurements show the appearance of an in-plane hcp-Co phase for nanowires with 50 nm diameter, suggesting a partial reorientation of the magnetocrystalline anisotropy axis along the membrane plane with increasing pore diameter. No significant changes in the magnetic behavior of the nanowire system are observed with decreasing temperature, indicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
56
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 39 publications
(66 reference statements)
6
56
2
Order By: Relevance
“…Among them, Cobased anisotropic nanomaterials are attracting a great part of scientific interest mainly for their possible applications as nanomagnets in (nano)medicine [10] and recording media [11], and as building blocks in high energy nanostructured bulk magnets [12]. All these studies showed that depending on the elaboration process, the nanowires can present very different size, shape, morphology and crystal symmetry as well as very different as-grown spacing between the nano-objects [7,[14][15][16][17][18][19][20][21][22]. Thus, altogether, those parameters give rise to a wide ensemble of magnetic behaviors that are far from being fully controlled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Cobased anisotropic nanomaterials are attracting a great part of scientific interest mainly for their possible applications as nanomagnets in (nano)medicine [10] and recording media [11], and as building blocks in high energy nanostructured bulk magnets [12]. All these studies showed that depending on the elaboration process, the nanowires can present very different size, shape, morphology and crystal symmetry as well as very different as-grown spacing between the nano-objects [7,[14][15][16][17][18][19][20][21][22]. Thus, altogether, those parameters give rise to a wide ensemble of magnetic behaviors that are far from being fully controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of a wide range of synthesis routes for the elaboration of controlled nano-objects, the number of studies trying to understand the zoology of the magnetic properties showed by these systems is continuously increasing [1][2][3][4][5][6][7][8][9]. Among them, Cobased anisotropic nanomaterials are attracting a great part of scientific interest mainly for their possible applications as nanomagnets in (nano)medicine [10] and recording media [11], and as building blocks in high energy nanostructured bulk magnets [12].…”
Section: Introductionmentioning
confidence: 99%
“…We also observe that for both samples H Cjj > H C\ , which is fully consistent with the shape anisotropy origin of the enhanced H C as discussed qualitatively within the Stoner-Wohlfarth model. 4 A comparable value of M R for both the samples could be attributed to the size effects. In the absence of size effects one would have expected a lower value of M R for sample 1 as compared to sample 2.…”
mentioning
confidence: 57%
“…[1][2][3] Bottom up self-assembly methods have been used to fabricate magnetic NW arrays of wire width ranging from single atom to several hundred nm are reported on a variety of templates. [1][2][3][4][5][6][7][8] Control over the size distribution of magnetic NWs has been demonstrated in carefully prepared porous anodized aluminum oxide (AAO) templates. 4,5 In AAO templates NW growth occurs perpendicular to the template surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation